Lung biodurability and free radical production of cellulose nanomaterials - Stefaniak, Aleksandr B. (Inhal Toxicol, 2014)
The potential applications of cellulose nanomaterials in advanced composites and biomedicine makes it imperative to understand their pulmonary exposure to human health. Here, we report the results on the biodurability of three cellulose nanocrystal (CNC), two cellulose nanofibril (CNF) and a benchmark cellulose microcrystal (CMC) when exposed to artificial lung airway lining fluid (SUF, pH 7.3) for up to 7 days and alveolar macrophage phagolysosomal fluid (PSF, pH 4.5) for up to 9 months. X-ray diffraction analysis was used to monitor biodurability and thermogravimetry, surface area, hydrodynamic diameter, zeta potential and free radical generation capacity of the samples were determined (in vitro cell-free and RAW 264.7 cell line models). The CMC showed no measurable changes in crystallinity (x(CR)) or crystallite size D in either SUF or PSF. For one CNC, a slight decrease in x(CR) and D in SUF was observed. In acidic PSF, a slight increase in x(CR) with exposure time was observed, possibly due to dissolution of the amorphous component. In a cell-free reaction with H(2)O(2), radicals were observed; the CNCs and a CNF generated significantly more (●)OH radicals than the CMC (p<0.05). The (●)OH radical production correlates with particle decomposition temperature and is explained by the higher surface area to volume ratio of the CNCs. Based on their biodurability, mechanical clearance would be the primary mechanism for lung clearance of cellulose materials. The production of (●)OH radicals indicates the need for additional studies to characterize the potential inhalation hazards of cellulose.